The Influence of Voice Gender and Hearer Gender on Voice‐Related Distress: Examining Gendered Interpersonal Dyads in Voice Hearing - Lucas Cabezas Klikovac; Mark Hayward (Clinical Psychology & Psychotherapy, 2026)
ABSTRACT Background Voice‐related distress has traditionally been explained by voice content and severity; however, emerging research highlights the importance of relational, social rank and gendered dynamics. This study examined whether the gender of the hearer and perceived voice gender interacted to influence distress and whether specific hearer gender–voice gender configurations were associated with heightened distress. Method Assessments within routine clinical practice were completed by 347 adults referred to a UK specialist clinic for distressing voices between 2016 and 2024. Participants provided data for gender (self and main voice) and voice‐related distress. Hypotheses were tested in relation to perceived voice gender, the pairing of hearer gender and voice gender and associated distress. Results Male voices were significantly more common, and men were more likely to hear male voices than women. Women who heard male voices reported the highest levels of distress. Conclusions Voice‐related distress appears to be influenced by gendered interpersonal dynamics. Women who hear male voices may be especially vulnerable and could benefit from more targeted, relationally informed support in clinical settings.